Impacts of unilateral U.S. carbon policies on agricultural sector greenhouse gas emissions and commodity markets - Marcel Adenauer; Michael K Adjemian; Shawn Arita; Wade Brorsen; Joseph Cooper; Gyuhyeong Goh; Berna Karali; Mindy Lyn Mallory; Wyatt Thompson; Jisang Yu (Environmental Research Letters)
This article analyzes the consequences of the United States implementing unilateral policies to reduce greenhouse gas (GHG) emissions from agriculture. The policy representation is based loosely on current and past policy initiatives that have subsidized GHG reductions and considered special treatment for sectors heavily involved in trade. To do so, our first step is to generate new estimates of key parameters, elasticities of demand and supply, that are critical to understanding interactions among agricultural commodities, such as between livestock and crop products, in this area of research and more broadly. We apply these parameters in a widely used economic model that estimates the effects of a unilateral U.S. agricultural GHG policy on both domestic and foreign markets as well as global GHG emissions. Livestock effects dominate, driving most U.S. livestock product consumer prices higher and causing mixed crop and crop product price effects. A unilateral policy increases food costs in the implementing country and, if applied to all supplies, domestic and imported, tends to raise prices elsewhere as well. Alternative implementation strategies, such as not imposing the costs on exports or not imposing the costs on imports, can lead to lower food prices and greater consumption in other countries, as well as have important implications for the overall GHG reductions achieved by the unilateral effort.